MANAGEMENTUL CUNOȘTINȚELOR ÎN INSTITUȚIILE INFODOCUMENTARE: CAZUL BIBLIOTECII MUNICIPALE „B.P. HASDEU” - TIMUȘ, absolventă, USM, Științe ale comunicării și informării; conf. univ. dr. Natalia GOIAN, USM, Angela (BIBLIOPOLIS, 2020)
The most important phenomenons of the development of the society: the knowledge and the organization, lead to the emergence of knowledge based on institutions, which include elements such collective intelligence, competence, group and sustainable development. The success of these institutions is due to the innovation, knowledge distribution and relations between the members of collective. The knowledge’s valorification represents the quality of results. As a support for the formation and continuing professional development serve the technic of discovering by the institution of the human potential.